Acidose ruminal subaguda em ovinos Santa Inês: estudo clínico, laboratorial e avaliação da laminite por termografia infravermelha e radiologia digital - Girardi, Annita Morais [UNESP] (2016)
This study evaluated the use of infrared termography and digital radiologic examination as early diagnostic tools for laminitis in sheep with experimentally induced subacute ruminal acidosis, and the effects of long-term ingestion of a high concentrate diet on clinical and laboratory variables. Seven adult ewes with permanent rumen cannula were used, which did not have any previous ingestion of concentrate feed. For the induction of ruminal acidosis, it was added to the roughage, 10% of concentrate feed until reach 80%, percentage held to the end of the 19-week experiment. Diarrhea signs were observed from fourth to 22nd day and laminitis from fifth to 24th day. Ruminal fluid was predominantly liquid, sour-smelling and yellowish. Initial increases of heart rate, sedimentation and flotation time, platelets, segmented neutrophils, AST, ALP, GGT, ionized calcium, magnesium, glucose, urea, triglycerides, indirect and total bilirubin were noted. At the beginning of the experiment, there was reduction of respiratory rate, lymphocytopenia, monocytopenia, hypocalcemia, hypophosphatemia, hyponatremia, hypoproteinemia, and hypocholesterolemia. Ruminal movement rate, methylene blue reduction time, creatinine, direct bilirubin, lactate and CK blood levels decreased, while body temperature, weight and score, eosinophils, albumin, chloride and potassium blood levels increase throughout the period. Ruminal pH reduction occurred within the first days, despite its maintenance above 5.5 during the 19 weeks. Respiratory and metabolic mechanisms, mainly urine acidification, remained the blood pH between physiologic limits for sheep. Sixteen protein fractions were separated by electrophoresis, among them eight proteins of unknown functions, identified by their molecular weights. Most acute phase proteins and the immunoglobulins identified in the electrophoretic fractionation varied throughout the observation period, suggesting inflammation. No macroscopic alteration was detected at necropsy. The digital radiology did not allow the identification of podal changes resulting from laminitis during the trial period. Infrared thermography has detected increases in the maximum temperature of the hoof wall, even without the clinical manifestation of pain, indicating that this technique can be an useful tool to detect laminitis in sheep at an early stage of the disease.